Land‐Use Change Impact on Soil Sustainability in a Climate and Vegetation Transition Zone. (1st November 2015) - Reitsma, K.D.; Dunn, B.H.; Mishra, U.; Clay, S.A.; DeSutter, T.; Clay, D.E.
Abstract : A growing world population and climate change are expected to influence future agricultural productivity and land use. This study determined the impact of land‐use change on soil sustainability and discussed the factors contributing to these changes. South Dakota was selected as a model system because corn ( Zea mays L.) grain prices tripled between 2006 and 2012 and it is located in a climate and grassland/cropland transition zone. High resolution imagery was used to visually determine land uses (cropland, grassland, nonagricultural, habitat, and water) at 14, 400 points in 2006 and 2012. At each point, land‐use change and the USDA land capability class (LCC) were determined. Over the 6‐yr study period, 6.87% of the grasslands (730, 000 ha) were converted to cropland, with 93% occurring on lands generally considered suitable for crop production (LCC ≤ IV) if appropriate practices are followed. Converted grasslands, however, had higher LCC values than existing croplands and lower LCC values than remaining grasslands. In addition, 4.2% of the croplands (250, 000 ha) were converted to grasslands, and statewide, 20, 000 ha of croplands were converted to grasslands in areas limited by excess water (LCC V). The conversion of grasslands could not be linked to one specific factor and may be related to: (i) a desire to increase financial returns, (ii) changes in the land ownership structure, (iii) technology improvements, (iv) governmental policies, (v) climate change, and (vi) an aging workforce. Research and outreach programs that balance the goods and services of different land uses are needed to maintain sustainable agroecosystems.